Role of miRNAs in Rheumatoid Arthritis Therapy - Yiping Zhang; Meiwen Yang; Hongyan Xie; Fenfang Hong; Shulong Yang (Cells, 2023)
Rheumatoid arthritis (RA) is a chronic systemic inflammatory disease characterized by autoimmunity, synovial inflammation and joint destruction. Pannus formation in the synovial cavity can cause irreversible damage to the joint and cartilage and eventually permanent disability. Current conventional treatments for RA have limitations regarding efficacy, safety and cost. microRNA (miRNA) is a type of non-coding RNA (ncRNA) that regulates gene expression at the post-transcriptional level. The dysregulation of miRNA has been observed in RA patients and implicated in the pathogenesis of RA. miRNAs have emerged as potential biomarkers or therapeutic agents. In this review, we explore the role of miRNAs in various aspects of RA pathophysiology, including immune cell imbalance, the proliferation and invasion of fibroblast-like synovial (FLS) cell, the dysregulation of inflammatory signaling and disturbance in angiogenesis. We delve into the regulatory effects of miRNAs on Treg/Th17 and M1/M2 polarization, the activation of the NF-κB/NLRP3 signaling pathway, neovascular formation, energy metabolism induced by FLS-cell-induced energy metabolism, apoptosis, osteogenesis and mobility. These findings shed light on the potential applications of miRNAs as diagnostic or therapeutic biomarkers for RA management. Furthermore, there are some strategies to regulate miRNA expression levels by utilizing miRNA mimics or exosomes and to hinder miRNA activity via competitive endogenous RNA (ceRNA) network-based antagonists. We conclude that miRNAs offer a promising avenue for RA therapy with unlimited potential.